Penerapan digital marketing dalam pemasaran snack basreng di kampus UIN Sumatera Utara - Muhammad Sinar Randi; Nur Hijryati Waisa; Salsabila Aulia; Winy Wiranti; Astrid Natasya (Institut Nalanda, 2024)
This study aims to analyze the application of digital marketing in marketing basreng snacks in the UIN Sumatera Utara Campus environment. Qualitative descriptive methods are used to document the marketing process from purchasing raw materials to distribution. With a capital of IDR 70,000.00, which includes raw materials of IDR 55,000.00 and plastic packaging of IDR 15,000.00, the business actor produces 17 packages of basreng weighing 250 grams per package. With a selling price of IDR 8,000.00 per package, the income reaches IDR 136,000.00, resulting in a net profit of IDR 66,000.00. Promotion is carried out through social media WhatsApp and Instagram. WhatsApp is used to reach direct contacts, while Instagram expands the reach of consumers through photo uploads and stories features. Transactions are carried out via Cash on Delivery (COD) in the campus environment, facilitating interaction with consumers. The results show that digital marketing increases sales at a low cost. Marketing diversification to e-commerce platforms is recommended to expand market reach and support business sustainability.